Efforts to Improve Student Learning Outcomes through the Application of the Contextual Teaching and Learning Model in Islamic Education Learning at SD Negeri 0105 Sibuhuan - Sayuti, Ahmad; Nasution, Siti Bagon; Rangkuti, Ummi Hani (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' learning outcomes in Islamic religious education learning through the application of the Contextual Teaching and Learning Learning Model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that through the Application of the Contextual Teaching and Learning Learning Model, it can improve students' learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, through the Application of the Contextual Teaching and Learning Learning Model, it can be used as an alternative to improve students' learning outcomes in Islamic religious education learning.